Neotypification of the name Diplomeris pulchella (Orchidaceae) - Kemprai, Kapil Kumar; Khersa, Bimisa; Bhuyan, Birina; Deori, Chaya; Chanu, Longjam Malemnganbee; Medhi, Pramod; Borah, Souravjyoti (Rheedea, 2026)
Diplomeris pulchella D.Don (Orchidaceae) was described with an obscure indication of the type, referring only to a Wallich collection from Nepal. Subsequent searches for Wallich specimens from Nepal failed to locate any relevant material. However, a specimen of D. pulchella collected by Wallich from Sylhet, Bangladesh, is preserved at BM. It remains uncertain whether Don mistakenly cited the locality as “Nepalia” instead of Sylhet, or whether the BM specimen does not represent original material. As the BM specimen cannot be confidently confirmed as original material, it is here designated as the neotype.